Pengaruh Komitmen Organisasional dan Lingkungan Psikologis Terhadap Produktivitas Kerja Karyawan - Dudung Abdullah (Papanda Publisher, 2022)
This research was conducted on employees of Bank BJB Majalengka Branch with the aim of knowing organizational commitment, psychological environment, and work productivity and to determine the effect of organizational commitment and psychological environment on work productivity either partially or simultaneously. The method used is a survey method and is designed as a descriptive verification study with qualitative and quantitative approaches. The population in this study were employees of Bank BJB Majalengka Branch, totalling 40 people. The data collection technique used a questionnaire. Instrument testing is done by testing the validity, reliability and normality of the data, while the data analysis uses the correlation coefficient and the coefficient of determination. Hypothesis testing uses a t-test for a partial test and F-test for a simultaneous test. The results of the study found that organizational commitment is in the high category, the psychological environment is in a good category, and productivity is in the high category. The results of hypothesis testing indicate that organizational commitment and psychological environment both simultaneously and partially have a positive and significant effect on the work productivity of employees of Bank BJB Majalengka Branch.